Word problems versus image-rich problems: an analysis of effects of task characteristics on students' performance on contextual mathematics problems. Issue 1 (2nd January 2018) - Hoogland, Kees; Pepin, Birgit; de Koning, Jaap; Bakker, Arthur; Gravemeijer, Koeno
ABSTRACT: This article reports on a post hoc study using a randomised controlled trial with 31, 842 students in the Netherlands and an instrument consisting of 21 paired problems. The trial showed a variability in the differences of students' results in solving contextual mathematical problems with either a descriptive or a depictive representation of the problem situation. In this study the relation between this variability and two task characteristics is investigated: (1) complexity of the task representation; and (2) the content domain of the task. We found indications that differences in performance on descriptive and depictive representations of the problem situation are related to the content domain of the problems. One of the tentative conclusions is that for depicted problems in the domain of measurement and geometry the inferential step from representation of the problem situation to the mathematical problem to be solved is smaller than for word problems.